Análisis de los riesgos laborables en la empresa Provenseric S.A en la ciudad de Quito, e implementación de mejoras - Gómez Valarezo, Cristian Stalin (2016)
This paper is structured of 5 chapters in which the following topics: Chapter 1, Situation of the Organization. In this chapter all information PROVENSERINC SA, historical review, its location, the products offered in the Ecuadorian market, its workers, its mission, vision and business objectives, detailed herein refers to all general information of the same. Chapter 2, Theoretical Framework. This chapter contains all the theoretical aspect, legal containing this work, general contents about the identification, measurement and assessment of occupational hazards in a particular company, as well as current legislation. Chapter 3, Analysis of Current Business Processes. This chapter contains the current state of business processes, on the other hand has the identification, measurement, and evaluation and measures of risk factors found in each job. Here you can find the Risk Matrix. Chapter 4, Proposed Process Improvement. This chapter describes the control measures taken to improve processes and jobs where significant risks that could cause harm to the worker in the short, medium and long term were found detailed. Finally, Chapter 5, Conclusions and Recommendations. The results and proposals for further improvement in processes where significant risks are found.